Implementation of an Ethical Circular Hub: Framework Proposal - Garrido, Susana; Nunes, Carmina S. (European Journal of Sustainable Development, 2023)
There are significant regional disparities regarding circular material use rates between Western European countries and other regions in the EU. Hence, there is a severe risk that the circular transition will remain slow and unevenly distributed across EU regions. Business ethics related to circular change involves some principles and practices that guide the ethical conduct of businesses operating within the circular economy. The study aims to recommend a framework to guide regional entities to implement an Ethical Circular Hub to identify new solutions and challenges regarding stakeholder collaboration, ethical circular value chains, social equity, fair labor practices, and transparency, suggesting innovative business models. This framework proposal is based on the literature review and analysis of case studies to identify and promote the best practices in terms of Ethical Circular Hubs implementation. The outcomes of this study will help improve the regional development of policy instruments in the field of Ethical Circular Hubs, identifying ethical and circular best practices to overcome transition problems, will enable countries’ regions to integrate and benchmark successful experiences and policies from other regions into their own regional reality and contribute to a more sustainable, resilient, and inclusive society. Keywords: ethics, circular economy, ethical circular hubs, social impact, policies